2018
DOI: 10.20937/rica.2018.34.04.07
|View full text |Cite
|
Sign up to set email alerts
|

MODELO DE DISTRIBUCIÓN ESPACIAL, TEMPORAL Y DE ESPECIACIÓN DEL INVENTARIO DE EMISIONES DE MÉXICO (AÑO BASE 2008) PARA SU USO EN MODELIZACIÓN DE CALIDAD DEL AIRE (DiETE)

Abstract: Palabras clave: contaminación atmosférica, emisiones, distribución horaria, distribución geográfica, distribución especies químicas RESUMEN Este trabajo presenta el modelo de distribución espacial, temporal y de especiación (DiETE) del Inventario de Emisiones de México para el año base 2008. Se describen tanto la metodología utilizada como la información empleada para realizar la distribución espacial, temporal y química de las emisiones. Se muestran los resultados de la aplicación de este modelo al Inventario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The data underpinning these spatial and temporal profiles are openly accessible via UNAM_EMI model created by the National Autonomous University of Mexico (UNAM) (García-Reynoso et al, 2018). The procedure for converting from annual to hourly can be found in García-Reynoso et al (2018). Leveraging this model, we have meticulously generated 3 km hourly CO 2,ff (fossil fuel CO 2 ) emissions profiles.…”
Section: Emission Inventories and Biogenic Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data underpinning these spatial and temporal profiles are openly accessible via UNAM_EMI model created by the National Autonomous University of Mexico (UNAM) (García-Reynoso et al, 2018). The procedure for converting from annual to hourly can be found in García-Reynoso et al (2018). Leveraging this model, we have meticulously generated 3 km hourly CO 2,ff (fossil fuel CO 2 ) emissions profiles.…”
Section: Emission Inventories and Biogenic Fluxesmentioning
confidence: 99%
“…The source code for the WRF version 3.9.1.1 model (freely available) are available https://www2.mmm.ucar.edu/wrf. Additionally, the source code for the UNAM_EMI model employed in this research (freely available) is detailed in García-Reynoso et al (2018), and the source code for the X-STILT model used in this study (freely available) can be found in Wu et al (2019). All figures were produced using the matplotlib package version 3.3.4 in Python 3.7, as introduced by Hunter (2007).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Para obtener una BDE útil en MCA, se aplicó al INEM-2013 la metodología descrita en el modelo DiETE (INECC 2017, García-Reynoso et al 2018, en el cual la distribución espacial de emisiones en cada celda del dominio de modelación se realiza con base en datos de población, cobertura de suelo y ubicación de industrias; para fuentes móviles, se considera la fracción de la malla correspondiente a las vialidades y carreteras; para la distribución temporal se emplean los códigos fuente Source Classification Codes (SCC) de la United States Environment Protection Agency (US-EPA), que contienen perfiles temporales mensuales, semanales y diarios por tipo de fuente.…”
Section: Metodología Para La Actualización Del Inventario De Emisionesunclassified
“…February 2011 month was modeled because more surface measurement data is available (from a campaign carried out in Mexico State). The parameterizations employed in this work are YSU-Scheme for the boundary layer (Song-You et al, 2006), the WRF Single-Moment 5-class scheme (WSM5) for microphysics (Song-You et al, 2004), the rapid and accurate radiative transfer model scheme (RRTM) for the longwave radiation (Mlawer et al, 1997), the Goddard scheme for the shortwave radiation (Matsui et al, 2018) and Grell-3 scheme for the cumulus option (Grell, 1993;Grell et al, 2002) The 2008 national emissions inventory (García et al, 2018) was used because at the time of the analysis only these emission data were available. The National Emissions Inventory was developed by the Ministry of Environment (SEMARNAT).…”
Section: Model and Data Descriptionmentioning
confidence: 99%